2022
DOI: 10.24072/pcjournal.134
|View full text |Cite
|
Sign up to set email alerts
|

Sexual coercion in a natural mandrill population

Abstract: Increasing evidence indicates that sexual coercion is widespread. While some coercive strategies are conspicuous, such as forced copulation or sexual harassment, less is known about the ecology and evolution of intimidation, where repeated male aggression promotes future rather than immediate mating success with targeted females. Although known in humans, intimidation was recently reported in chimpanzees (Pan troglodytes) and chacma baboons (Papio ursinus), where males are regularly violent against females. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 80 publications
2
20
1
Order By: Relevance
“…In particular, when females have some reproductive control (i.e., control over when and with whom to mate), as in most lemurs (Hohenbrink et al, 2016;Lewis et al, 2022), they typically have more leverage when sexually receptive because males who try to mate with them may avoid to aggress them (Lewis, 2002;Davidian et al, 2022). Yet, additional results show that sexually receptive female mandrills are not more likely to win conflicts against males compared to females in other reproductive states, possibly because they have low reproductive control due to frequent sexual coercion (Smit et al, 2022). Instead, this result may reflect demographic changes due to the influx of male mandrills in the social group at the beginning of that season.…”
Section: Figurementioning
confidence: 83%
See 4 more Smart Citations
“…In particular, when females have some reproductive control (i.e., control over when and with whom to mate), as in most lemurs (Hohenbrink et al, 2016;Lewis et al, 2022), they typically have more leverage when sexually receptive because males who try to mate with them may avoid to aggress them (Lewis, 2002;Davidian et al, 2022). Yet, additional results show that sexually receptive female mandrills are not more likely to win conflicts against males compared to females in other reproductive states, possibly because they have low reproductive control due to frequent sexual coercion (Smit et al, 2022). Instead, this result may reflect demographic changes due to the influx of male mandrills in the social group at the beginning of that season.…”
Section: Figurementioning
confidence: 83%
“…Regarding methodological problems, mandrills live in exceptionally large groups and in dense forests with low visibility, making it difficult to observe interactions between all group members. Additionally, intersexual aggression is characterized by relatively low severity (Smit et al, 2022) and thus it might be easily overlooked outside focal observations. As a result, a majority (62%) of the intersexual dyads in our study group were never observed interacting agonistically (Supplementary Table S1), and such proportion is highest (92%) in those dyads where the female was found to outrank the male.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations